Anti-Corruption Education: A Bottom-Up Approach in Purworejo Regency, Indonesia - Manotar Tampubolon; Bibit Samad Rianto (Budapest International Research and Critics University, 2022)
Many government and non-governmental entities have already introduced community outreach to prevent corrupt practices by raising public awareness and encouragement in recent years. The issue would be that the anti-corruption consultation could empower society to stop corruption. The primary aim of such counseling would be to create a better understanding and conformance to village officers concerning types of corruption, the dangers of corruption, the law, the risks associated with crime, and alternative prevention. The method used in this outreach is a participatory method that includes lectures, discussions, and questions and answers. I aim this community outreach at 343 Village Heads in Purworejo Regency, Central Java, Indonesia for the 2019-2024 term of service. This program facilitates participants about anti-corruption measures. Despite some challenges that village heads face in managing village funds, these outreach efforts have significantly affected promoting anti-corruption efforts in Purworejo Regency. An effective anti-corruption intervention that involves village officials is a step toward developing anti-corruption understanding at the village level and transforming it into an Anti-Corruption Village. As a result, the village head must be one of the anti-corruption components, laying the groundwork for a more robust National Integrity System.